2012
DOI: 10.1051/epjconf/20122405005
|View full text |Cite
|
Sign up to set email alerts
|

7Be atmospheric concentration at mid latitudes (40°N) during a year of solar minimum

Abstract: In this paper we present the variation of 7 Be concentration in the surface air of Thessaloniki, Greece (40 • 62 N,22 • 95 E) over the year 2009, a year of a deep solar minimum, and, as a consequence, a year of maximum concentration of 7 Be in surface air. The mean annual activity concentration of 7 Be for the year 2009 was 6.0 mBq m −3 . The relative variability of 7 Be surface concentration related to the solar cycle was calculated to be deviated by about 20% from maximum to mean. A positive correlation (R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The correlation observed with the precipitations is supported by recent studies, which found a strong correlation between precipitations and 7 Be deposition fluxes (Chen et al, 2016;Zhang et al, 2016). In constrast, many studies have found a non-significant correlation between 7 Be row data and the total monthly precipitation per month (Azahra et al, 2004b;Ali et al, 2011;Pham et al, 2011;Kotsopoulou and Ioannidou, 2012).…”
Section: 1supporting
confidence: 66%
See 2 more Smart Citations
“…The correlation observed with the precipitations is supported by recent studies, which found a strong correlation between precipitations and 7 Be deposition fluxes (Chen et al, 2016;Zhang et al, 2016). In constrast, many studies have found a non-significant correlation between 7 Be row data and the total monthly precipitation per month (Azahra et al, 2004b;Ali et al, 2011;Pham et al, 2011;Kotsopoulou and Ioannidou, 2012).…”
Section: 1supporting
confidence: 66%
“…Thus, the seasonal-trend decomposition reveals the strong influence of temperature on the seasonal variability of the 7 Be air concentration. Many studies have observed a negative correlation between 7 Be air concentration and relative humidity (Dueñas et al, 2009;Kotsopoulou and Ioannidou, 2012;Piñero-García and Ferro-García, 2012). However, in this study RH is positively correlated with the seasonal component ( = 0.60).…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation
“…Ioannidou et al, 2014), persistence of anticyclone conditions (no wet removal of aerosol particles) and higher convection (warm air transported upwards and cold air from the upper troposphere transported downwards), and the stratospheric intrusions during tropopause folding events govern the occurrence of maximum values, while, on the other hand, typical processes of the cold period, such as high relative humidity conditions, resulting in increased particle sizes of atmospheric aerosols, and so, higher scavenging rate of aerosols, or the occurrence of strong rainfall events can cause the decreased activity concentrations in the surface air (Kotsopoulou and Ioannidou, 2012).…”
Section: Monthly Index Analysismentioning
confidence: 99%
“…Be is a cosmogenic radionuclide formed by spallation reactions of light atmospheric nuclei (such as carbon, nitrogen and oxygen) with very high-energy protons and neutrons of the primary cosmic rays(Lal et al, 1958;Bruninx, 1961). Most7 Be production (∼70%) occurs in the stratosphere and the remainder (∼30%) is produced in the troposphere, so that the7 Be production rate is altitude-dependent(Feely et al, 1989;Baeza et al, 1996;Kotsopoulou & Ioannidou, 2012).…”
mentioning
confidence: 99%